Bivalirudin for acute coronary syndromes: premises, promises and doubts - Capodanno, Davide; Caterina, Raffaele De (Thrombosis and Haemostasis, 2015)
Bivalirudin is a valuable anticoagulant option in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary intervention. Advantages over heparin as a parenteral anticoagulant include more predictable pharmacokinetics and pharmacodynamics, shorter half-life, no need for cofactors, some degree of antiplatelet effect, and the ability to inhibit clot-bound thrombin. Clinical evidence supporting the use of bivalirudin over heparin in current ACS guidelines, however, derives mostly from early randomised trials that may no longer reflect current management patterns, now including the use of oral antiplatelet agents more potent than clopidogrel (i.e. prasugrel or ticagrelor) and a broader implementation of strategies to reduce bleeding (i.e. radial access for percutaneous coronary intervention, and use of glycoprotein IIb/IIIa inhibitors only in bailout situations). Defining the fine balance between bivalirudin efficacy and safety over heparins in the context of other antithrombotic treatments remains a challenge in clinical practice, particularly in a fast-evolving scenario, such as ACS, where numerous new trials have been presented in very recent times. Here we provide an up-to-date overview of the evidence on the use of bivalirudin in ACS, with focus on new data, open issues, and future directions.
Keywords: Bivalirudin; anticoagulants; heparin; acute coronary syndromes; percutaneous coronary intervention